2022
DOI: 10.1111/head.14311
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre‐morbid headaches on headache features and long‐term health outcomes following traumatic brain injury: Insights from the American Registry for Migraine Research

Abstract: Objective: To investigate the impact of having headaches prior to traumatic brain injury (TBI) on headache features and long-term patient health outcomes. Background and Methods: This was an exploratory analysis of patients with TBI who were enrolled in the American Registry for Migraine Research (ARMR), a multicenter, prospective, longitudinal patient registry composed of patients with International Classification of Headache Disorders, 3rd edition (ICHD-3)-defined headache diagnoses. The ARMR study enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Per ARMR inclusion criteria, patients were 18 years of age or older, fluent in English, had a primary or secondary headache disorder diagnosis, could access a computer or comparable device with Internet access, and were able and willing to provide informed consent. Previous reports of these data have analyzed mild traumatic brain injury, 15,16 depression and anxiety, 17 white matter hypersensitivities, 18 and broad findings of the study 14 …”
Section: Methodsmentioning
confidence: 99%
“…Per ARMR inclusion criteria, patients were 18 years of age or older, fluent in English, had a primary or secondary headache disorder diagnosis, could access a computer or comparable device with Internet access, and were able and willing to provide informed consent. Previous reports of these data have analyzed mild traumatic brain injury, 15,16 depression and anxiety, 17 white matter hypersensitivities, 18 and broad findings of the study 14 …”
Section: Methodsmentioning
confidence: 99%
“…The ICHD-3 criteria for PTH account for a common clinical scenario in which individuals have headaches prior to their mTBI. This scenario is frequent [5,6] because migraine is a common disease with a prevalence of 14.0% in the general population [7] and preexisting migraine is a risk factor for developing PTH [12]. When a person has pre-TBI headaches that substantially worsen following a TBI, the individual receives two headache diagnoses: a diagnosis of preinjury headache, such as migraine or tension-type headache (TTH), and PTH.…”
Section: Clinical Presentation Of Posttraumatic Headache and Overlap ...mentioning
confidence: 99%
“…This aspect of PTH should be investigated rigorously, as the overlap of PTH and migraine has led to the underdiagnosis of PTH. An observational study within the American Registry for Migraine Research demonstrated that amongst 565 participants with TBI (93.3% of whom received a migraine diagnosis), 25.7% reported new or worsening headaches within seven days of their injury [5]. However, only 17.2% of these individuals received a PTH diagnosis, with those who had headaches prior to their TBI being less likely to receive a PTH diagnosis compared to those without pre-TBI headaches.…”
Section: Clinical Presentation Of Posttraumatic Headache and Overlap ...mentioning
confidence: 99%
See 1 more Smart Citation
“…His research interests include traumatic brain injury and posttraumatic headache. We hope to see much more from him down the road, in his long career ahead! 3 …”
mentioning
confidence: 97%